2020
DOI: 10.1101/2020.05.11.054619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensorimotor hallucinations in Parkinson’s disease

Abstract: Hallucinations in Parkinson's disease (PD) are one of the most disturbing non-motor symptoms, affect half of the patients, and constitute a major risk factor for adverse clinical outcomes such as psychosis and dementia. Here we report a robotics-based approach, enabling the induction of a specific clinically-relevant hallucination (presence hallucination, PH) under controlled experimental conditions and the characterization of a PD subgroup with enhanced sensorimotor sensitivity for such robot-induced PH. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Previous work has shown that the robot-induced FoP results from the manipulation of sensory and motor stimuli, which involve tactile stimulation on the back, as well as proprioceptive, tactile, and motor cues (from the upper limb), the congruency of which in the spatial and temporal domains are controlled via the robot. In the current and our previous research Salomon et al, 2020;Bernasconi et al, 2020), two main experimental conditions were used (synchronous and asynchronous sensorimotor stimulation). Both conditions contain a spatial conflict (between the spatial position of the moving hand and the spatial position of the touch cue delivered on the back of the participants), whereas the asynchronous condition also contains an additional spatiotemporal conflict (i.e., movement performed by the hand is delivered to the back of the participants with a delay of 500 ms).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that the robot-induced FoP results from the manipulation of sensory and motor stimuli, which involve tactile stimulation on the back, as well as proprioceptive, tactile, and motor cues (from the upper limb), the congruency of which in the spatial and temporal domains are controlled via the robot. In the current and our previous research Salomon et al, 2020;Bernasconi et al, 2020), two main experimental conditions were used (synchronous and asynchronous sensorimotor stimulation). Both conditions contain a spatial conflict (between the spatial position of the moving hand and the spatial position of the touch cue delivered on the back of the participants), whereas the asynchronous condition also contains an additional spatiotemporal conflict (i.e., movement performed by the hand is delivered to the back of the participants with a delay of 500 ms).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that the present results cannot be due to differences in motor patterns spontaneously adopted by participants during the synchronous versus the asynchronous stimulation condition. Indeed, data collected with the same robotic system show that there is no difference in the quantity of poking movements performed in the two conditions, and that there is no link between movement characteristics and the induced FoP (Bernasconi et al, 2020).…”
Section: Access Isciencementioning
confidence: 97%
See 1 more Smart Citation